Social and structural barriers and facilitators to HIV healthcare and harm reduction services for people experiencing syndemics in Manitoba: study protocol - Linda Larcombe; Laurie Ireland; Ken Kasper; Yoav Keynan; Neora Pick; Michael Payne; Jared Bullard; Kathleen Deering; Julianne Sanguins; Katharina Maier; Andrea Krüsi; Zulma Vanessa Rueda; et al. (BMJ Open)
Introduction In Manitoba, Canada, there has been an increase in the number of people newly diagnosed with HIV and those not returning for regular HIV care. The COVID-19 pandemic resulted in increased sex and gender disparities in disease risk and mortalities, decreased harm reduction services and reduced access to healthcare. These health crises intersect with increased drug use and drug poisoning deaths, houselessness and other structural and social factors most acutely among historically underserved groups. We aim to explore the social and structural barriers and facilitators to HIV care and harm reduction services experienced by people living with HIV (PLHIV) in Manitoba.Methods and analysis Our study draws on participatory action research design. Guiding the methodological design are the lived experiences of PLHIV. In-depth semi-structured face-to-face interviews and quantitative questionnaires will be conducted with two groups: (1) persons aged ≥18 years living or newly diagnosed with HIV and (2) service providers who work with PLHIV. Data collection will include sex, gender, sociodemographic information, income and housing, experiences with the criminal justice system, sexual practices, substance use practices and harm reduction access, experiences with violence and support, HIV care journey (since diagnosis until present), childhood trauma and a decision-making questionnaire. Data will be analysed intersectionally, employing grounded theory for thematic analysis, sex-based and gender-based analysis and social determinants of health and syndemic framework to understand the experiences of PLHIV in Manitoba.Ethics and dissemination We received approval from the University of Manitoba Health Ethics Research Board (HS25572; H2022:218), First Nations Health and Social Secretariat of Manitoba, Nine Circles Community Health Centre, Shared Health Manitoba (SH2022:194) and 7th Street Health Access Centre. Findings will be disseminated using community-focused knowledge translation strategies identified by participants, peers, community members and organisations, and reported in conferences, peer-reviewed journals and a website (www.alltogether4ideas.org).